A State of Art Review on Machine Learning Algorithms for Solving Classification Problems - Putta Durga (AG Volumes, 2022)
It is a job of “natural language processing” to use machine learning techniques to classify sentences. Sentiment analysis is one of the most common categorization jobs, however there are many more. Because each algorithm is utilised to tackle a particular issue, a distinct algorithm is generally required for each job. The proper algorithm should be chosen for each task. Is there a way to accomplish this? Multiple methods and parameter settings may be tested if your computer has a lot of processing power. A fundamental concern in this method is how to accurately measure and evaluate the effectiveness of algorithms. Hence, this paper presents a review on the various machine learning algorithms that are being used for solving classification problems.